Sparks and Taylor's nursing diagnosis reference manual - Ralph, Sheila Sparks; Taylor, Cynthia M. (Wolters Kluwer Health/Lippincott Williams & Wilkins, 2014)
Provides care plan guidelines for all 2012-2014 NANDA International (NANDA-I) approved nursing diagnoses